Patients Access to Medicines – A Critical Review of the Healthcare System in Kenya - Toroitich AM; Dunford L; Armitage R; Tanna S (Dove Medical Press, 2022)
Anthony Martin Toroitich,1,2 Louise Dunford,3 Rachel Armitage,4 Sangeeta Tanna2 1Trade Affairs Department, Pharmacy and Poisons Board, Nairobi, Kenya; 2Leicester School of Pharmacy, De Montfort University, Leicester, UK; 3Leicester School of Allied Health Sciences, De Montfort University, Leicester, UK; 4Faculty of Health and Life Sciences, De Montfort University, Leicester, UKCorrespondence: Anthony Martin Toroitich, Leicester School of Pharmacy, De Montfort University, The Gateway, Leicester, LE1 9BH, UK, Tel +254724065344, Email P2539250@my365.dmu.ac.ukAbstract: Access to affordable, safe, effective, and quality-assured medicines by a patient is important for good health outcomes. Unfortunately, there is sparse literature published on the pharmaceutical enablers that may increase the sale of a substandard and falsified (SF) medicine to a patient in Kenya. The review highlights some of the factors that may facilitate the entry of SF medicines into the legitimate pharmaceutical supply chain and discusses their impact on patient access to medicines. Lack of essential medicines in public health facilities is an important factor that may contribute to increased demand for medicine-related out-of-pocket expenses from private health facilities, thus a likelihood for a patient purchasing SF medicine from unlicensed and illegal medicine outlets or unregulated websites. The need to increase medicine availability in the public sector by the Ministry of Health (MOH) is emphasized in addition to the strengthening of public procurement to cushion it from corruption and mismanagement. In addition, the MOH should promote local pharmaceutical manufacturing and implement a medicine pricing containment policy to avoid abuse and prevent overexploitation of patients, increase medicine price transparency, and reduce pharmaceutical supply chain distortion. Recommended regulatory reviews include accreditation of unlicensed illegal medicine outlets to facilitate accountability, regulatory oversight, and active surveillance. The national post-market surveillance regulatory capacity should be strengthened to improve rational medicine use. A 3-year diploma course should be replaced with a shorter 1- or 2-year pharmaceutical support staff training not eligible to superintend a pharmacy. The recommended legislative review includes a mandatory clause to enforce generic prescribing and the implementation of generic substitution by health workers. Unethical manipulative pharmaceutical marketing practices should carry stiffer penalties to deter malpractice. Future research areas include investigation of medicine prescribing and dispensing practices, medicine consumption studies, medicine price differences within different health sub-sectors, and between licensed pharmacies and unlicensed illegal medicine outlets.Keywords: substandard and falsified medicines, pharmacy practice, regulation, pharmaceutical supply chain